1983
DOI: 10.1093/jac/11.suppl_a.217
|View full text |Cite
|
Sign up to set email alerts
|

The pharmacokinetics of cefotetan excretion in the unobstructed biliary tree

Abstract: Cefotetan excretion was studied in 17 patients undergoing biliary or pancreatic surgery. The antibiotic was detected in bile taken from the common bile duct within 15 min of a 1 g iv bolus and therapeutic plasma levels were found up to 10 h after administration. Even higher concentrations of cefotetan were measured in the bile from functioning gall bladders, despite the presence of gall stones. Concentrations of cefotetan in bile from the common bile ducts and functioning gall bladders were greater than the pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1985
1985
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Based on the observed mean CLR for group I and a reported protein binding of approximately 88% (16) in normal volunteers, cefotetan undergoes urinary excretion primarily by glomerular filtration but with some tubular secretion. The major route of nonrenal elimination probably is biliary excretion, because it has been shown that cefotetan rapidly appears in the bile in high concentrations after intravenous dosing in humans (12,14).…”
Section: Methodsmentioning
confidence: 99%
“…Based on the observed mean CLR for group I and a reported protein binding of approximately 88% (16) in normal volunteers, cefotetan undergoes urinary excretion primarily by glomerular filtration but with some tubular secretion. The major route of nonrenal elimination probably is biliary excretion, because it has been shown that cefotetan rapidly appears in the bile in high concentrations after intravenous dosing in humans (12,14).…”
Section: Methodsmentioning
confidence: 99%
“…It is also excreted in the bile. Owen et al [70] studied the cefotetan excretion in patients who had undergone biliary or pancreatic surgery. Cefotetan was detected in bile taken from the common bile duct within 15 min of a 1-gram intravenous bolus.…”
Section: Less Commonly Used Cephalosporinsmentioning
confidence: 99%